A Protective Role of Arecoline Hydrobromide in Experimentally Induced Male Diabetic Rats. (28th January 2015) - Saha, Indraneel; Das, Joydeep; Maiti, Biswaranjan; Chatterji, Urmi
Abstract : Objectives. Arecoline, the most potent and abundant alkaloid of betel nut, causes elevation of serum testosterone and androgen receptor expression in rat prostate, in addition to increase in serum insulin levels in rats, leading to insulin resistance and type 2 diabetes-like conditions. This study investigated the role of arecoline on the reproductive status of experimentally induced type 1 diabetic rats. Methods. Changes in the cellular architecture were analyzed by transmission electron microscopy. Blood glucose, serum insulin, testosterone, FSH, and LH were assayed. Fructose content of the coagulating gland and sialic acid content of the seminal vesicles were also analyzed. Results. Arecoline treatment for 10 days at a dose of 10 mg/kg of body weight markedly facilitated β -cell regeneration and reversed testicular and sex accessory dysfunctions by increasing the levels of serum insulin and gonadotropins in type 1 diabetic rats. Critical genes related to β -cell regeneration, such as pancreatic and duodenal homeobox 1 ( pdx-1 ) and glucose transporter 2 ( GLUT-2 ), were found to be activated by arecoline at the protein level. Conclusion. It can thus be suggested that arecoline is effective in ameliorating the detrimental effects caused by insulin deficiency on gonadal and male sex accessories in rats with type 1 diabetes.